Methylene blue ameliorates colonic injury in acetic acid-induced colitis model - Tanrıkulu, Yusuf; Şen Tanrıkulu, Ceren; Kılınç, Fahriye; Can, Murat; Köktürk, Fürüzan; Kargın, Süleyman; Yılmaz, Gökhan (Bayrakol Medical Publisher, 2022)
Aim: Inflammatory bowel disease (IBD) is a serious health problem affecting the quality of life. IBDs caused by various pathophysiological mechanisms, including genetic, immunological, inflammatory, and environmental factors. Although it has been widely investigated, treatment of IBDs remains a difficult clinical problem. We aimed to investigate the healing of mucosal damage and anti-inflammatory effects of methylene blue (MB) in experimental colitis model. Material and Methods: Twenty-eight rats were randomly divided into four equal groups: group 1 (Sham), group 2 (control), group 3 (topical treatment), and group 4 (topical and systemic treatment). In groups 2, 3, and 4, acetic acid-induced colitis model was created. Normal saline to group 2, topical MB to group 3, and topical and systemic MB to group 4 were given. Results: The levels of hydroxyproline were lower in the treatment groups than in the control group (p=0.017 for group 3 and p=0.004 for group 4). There was no difference between groups according to the TNF- alpha levels. The results of macroscopic scores were significantly lower in treatment groups (group 3-4) than In the control group (group 2) (p=0.005 for group 3 and p=0.002 for group 4). There was a significant difference between the treatment groups and the control group according to the epithelial loss and inflammatory infiltrate (p=0.022 for group 3, p=0.026 for group 4 for both histopathological values). Discussion: MB ameliorates colonic injury in acetic acid-induced colitis model This effect of MB was observed both locally and with local + systemic administration.
Keywords: Acetic Acid; Colitis; Inflammatory Bowel Disease; Methylene Blue; TNF-?